To find the value of y that would make the expression equivalent to 5b+2, we first need to simplify the given expression:
yb-6 + 7 + 2b -3b + 1
Combine like terms:
yb + 2b - 3b - 6 + 7 + 1
y - b + 2
Now, set the simplified expression equal to 5b + 2 and solve for y:
y - b + 2 = 5b + 2
Subtract 2 from both sides:
y - b = 5b
Add b to both sides:
y = 5b + b
y = 6b
Therefore, the value of y that would make the expression equivalent to 5b + 2 is 6b.
What value of y would make the expression yb−6+7+2b−3b+1 equivalent to 5b+2 ?(1 point)
$$
1 answer